Association between urinary prostaglandin E(2) metabolite and breast cancer risk: a prospective, case-cohort study of postmenopausal women - Kim, Sangmi (2013)
Overweight or obese women are at increased risk of developing and dying from breast cancer. Obesity-driven inflammation may stimulate prostaglandin E(2) (PGE(2))-mediated aromatase activation and estrogen biosynthesis in breast tissues. We hypothesized that increased production of PGE(2) would contribute to elevated breast cancer risk in postmenopausal women. We carried out a case-cohort study with 307 incident breast cancer cases and 300 subcohort members from the Sister Study cohort. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated for the association between urinary levels of a major PGE(2) metabolite (PGE-M) and breast cancer risk using Prentice’s pseudo-likelihood approach. Several lifestyle factors were associated with urinary levels of PGE-M: smoking, high saturated fat diet and obesity increased urinary PGE-M, and use of nonsteroidal anti-inflammatory drugs (NSAIDs) decreased urinary PGE-M. Although there was no association between urinary PGE-M and postmenopausal breast cancer risk in the overall analysis or among regular users of NSAIDs, there was a positive association among postmenopausal women who did not regularly use NSAIDs with HRs of 2.1 (95% CI: 1.0–4.3); 2.0 (95% CI: 1.0–3.9); and 2.2 (95% CI: 1.1–4.3) for the second, third, and highest quartiles of PGE-M. Our findings suggest a link between systemic PGE(2) formation and postmenopausal breast cancer, and a possible modification of the association by lifestyle and pharmacological interventions. If confirmed in larger studies, these results may have useful implications for the development of preventive strategies.